THE EVOLUTION OF LITERARY CRITICISM DURING THE TWENTIETH CENTURY. - Mizrabova Jeren Ismailovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:This study offers a systematic examination of the origins and historical development  of  women’s  literary  tradition  alongside  feminist  criticism  within European and American cultural and historical frameworks. It analyzes the principal phases in the evolution of feminist theoretical discourse in literary studies, beginning with  early  manifestations  of  women’s  writing  and  the  emergence  of  critical  self-consciousness, and extending to the formal institutionalization of feminist discourse in the twentieth century.